Penerapan Praktik Keperawatan Keluarga melalui Intervensi Foot Massage dan Rendam Kaki Air Hangat Jahe dengan Pendekatan Family Empowerment pada Lansia Hipertensi di Wilayah Kerja Puskesmas Air Putih Samarinda - Regina Nur Azizah; Kartika Setia Purdani (Jurnal Kesehatan Amanah, 2026)
Hypertension is one of the major health problems among the elderly and poses a significant risk of serious complications if not properly managed. In addition to pharmacological therapy, safe, simple, and independent non-pharmacological approaches involving family participation are needed. This study aimed to analyze family nursing practice through a family empowerment approach using innovative interventions of foot massage and warm ginger foot soak to reduce blood pressure among elderly families with hypertension in the working area of Air Putih Public Health Center, Samarinda. The method used was a family nursing case study applying the nursing process approach. The interventions were conducted over three visits, including family education, foot massage training, and warm ginger foot soak therapy. The results showed a decrease in both systolic and diastolic blood pressure after the interventions, as well as an improvement in family knowledge and independence in caring for family members with hypertension. It can be concluded that the combination of foot massage and warm ginger foot soak based on family empowerment is effective as a complementary non-pharmacological therapy in controlling blood pressure among elderly patients with hypertension.